Regulating Extra‐Framework Cations in Faujasite Zeolites for Capture of Trace Carbon Dioxide. Issue 50 (13th July 2022) - Liu, Shanshan; Chen, Yinlin; Yue, Bin; Wang, Chang; Qin, Bin; Chai, Yuchao; Wu, Guangjun; Li, Jiangnan; Han, Xue; da‐Silva, Ivan; Manuel, Pascal; Day, Sarah J.; et al.
Abstract: The development of cost‐effective sorbents for direct capture of trace CO2 (<1 %) from the atmosphere is an important and challenging task. Natural or commercial zeolites are promising sorbents, but their performance in adsorption of trace CO2 has been poorly explored to date. A systematic study on capture of trace CO2 by commercial faujasite zeolites reveals that the extra‐framework cations play a key role on their performance. Under dry conditions, Ba−X displays high dynamic uptake of 1.79 and 0.69 mmol g −1 at CO2 concentrations of 10000 and 1000 ppm, respectively, and shows excellent recyclability in the temperature‐swing adsorption processes. K−X exhibits perfect moisture resistance, and >95 % dry CO2 uptake can be preserved under relative humidity of 74 %. In situ solid‐state NMR spectroscopy, synchrotron X‐ray diffraction and neutron diffraction reveal two binding sites for CO2 in these zeolites, namely the basic framework oxygen atoms and the divalent alkaline earth metal ions. This study unlocks the potential of low‐cost natural zeolites for applications in direct air capture. Abstract : The explicit structure‐performance relationship and underlying mechanism of trace CO2 capture by faujasite zeolites are elucidated. Two robust adsorbents are screened out, namely Ba−X with high dynamic CO2 uptake and K−X with unprecedented resistance to moisture.